2021
DOI: 10.1017/jfm.2021.194
|View full text |Cite|
|
Sign up to set email alerts
|

Three-dimensional turbulence without vortex stretching

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
(81 reference statements)
4
14
0
Order By: Relevance
“…One might obviously question the relevance of turbulence without vortex stretching to realistic turbulent flows. We have discussed this to some extent previously (Bos 2021). Reasons to further investigate this system are actually numerous.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…One might obviously question the relevance of turbulence without vortex stretching to realistic turbulent flows. We have discussed this to some extent previously (Bos 2021). Reasons to further investigate this system are actually numerous.…”
Section: Introductionmentioning
confidence: 91%
“…The proof of this requires that forces applied to the system are irrotational (Moffatt 1969). The system considered in the present investigation can be seen as the Euler equation to which we apply a force which compensates for vortex stretching at every point in space (Bos 2021). Because the curl of this force is equal to (minus) the vortex-stretching term in the vorticity equation, it is easily observed that this force is not irrotational, and helicity in the present system is therefore not conserved in closed vortex tubes.…”
Section: Conservation Of Integral Quantitiesmentioning
confidence: 99%
See 3 more Smart Citations